2008
DOI: 10.1159/000136002
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Options for Breast Cancer during Pregnancy

Abstract: National and international guidelines for pregnant breast cancer patients recommend to treat pregnant patients as closely as possible to the standards for non-pregnant patients. Therefore, new treatment options like sentinel lymph node biopsy or taxane-based chemotherapy have to be carefully checked for their possible implementation even for pregnant patients. These patients need to be treated in a breast cancer center where a multidisciplinary team is ready to support the patient and her family and to serve h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
1
12
0
4
Order By: Relevance
“…Our data have shown that around 1/3 of the patients with BCP had a HER2-positive disease. The use of trastuzumab during pregnancy is not advocated, as the majority of cases treated accidentally with trastuzumab during pregnancy showed an oligo-anhydramnios [35]. Recent data from the HERA study showed that, in the 16 pregnancies that occurred while treated with trastuzumab or up to 3 months after the end of trastuzumab treatment, no oligohydramnios occurred in the 5 women who continued pregnancy [36].…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Our data have shown that around 1/3 of the patients with BCP had a HER2-positive disease. The use of trastuzumab during pregnancy is not advocated, as the majority of cases treated accidentally with trastuzumab during pregnancy showed an oligo-anhydramnios [35]. Recent data from the HERA study showed that, in the 16 pregnancies that occurred while treated with trastuzumab or up to 3 months after the end of trastuzumab treatment, no oligohydramnios occurred in the 5 women who continued pregnancy [36].…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Other drugs, like the pyrimidine-antagonist 5-fluorouracil, should be avoided during pregnancy because of limited experience in pregnancy [10,11,16,17,49]. For other drugs, reports are contradictory, e.g.…”
Section: Fetus · Renal Insufficiency · Trastuzumab · Breast Cancer · mentioning
confidence: 99%
“…Neonatal defects from tamoxifen have been described in the genital tract in female mice. Although tamoxifen has safely been given in patients with metastatic breast cancer without damage to the child, there are other reports of birth defects such as Goldenhar syndrome and ambiguous genitalia in children born to women exposed to tamoxifen [4]. Radiation exposure in the 1st trimester of gestation has been associated with an increased risk of mental retardation and fetal malformation.…”
Section: Introductionmentioning
confidence: 99%
“…Ondansetron has the longest safety record, and no increased frequency of adverse effects has been reported in connection with treating pregnant patients [4].…”
Section: Introductionmentioning
confidence: 99%